Extrinsic Motivation and its Association with the Teaching Quality, Student Attitude and Academic Performance in Engineering Students (2018)
The association between extrinsic motivation, teaching quality, student attitude and academic performance was analyzed in 950 students of the engineering programs of the University of Cartagena between 2014 and 2016. The instrument to measure extrinsic motivation was evaluated through the CEVEAPEU questionnaire (questionnaire for the evaluation of learning strategies of university students) developed and validated by Gargallo et. al (2009) which was modified for the research requirements and validated by Alfa de Cronbach. The teaching quality and academic performance were evaluated by means of a survey, while the student attitude was evaluated by means of the instrument designed by Lindner et al (1993) called "Inventory of Self-regulation of Learning" incorporating elements of Boza & de la O Toscano (2012). For the relationship analysis, the variables were crossed and the bar diagrams and the 2x2 contingency tables were constructed applying the Chi-Square independence test. The values of 0.91, 0.85, 0.89 and 0.88 for the Cronbach's Alpha allowed to validate the instruments used. The results indicate that there is a significant degree of statistical significance (p <0.05) between extrinsic motivation and teaching quality (p = 0.0002) and student attitude (p = 0.0000) at a confidence level of 95%. This means that extrinsic motivation and teaching quality are associated statistically due to the pedagogical quality and quality teacher training of the professors of the faculty of engineering. On the other hand, the positive attitude that engineering students have, It has allowed the establishment of a statistical association between extrinsic motivation and student attitude.